A novel global maximum power point tracking strategy (GMPPT) based on optimal current control for photovoltaic systems adaptive to variable environmental and partial shading conditions. (1st March 2017) - Zhao, Jian; Zhou, Xuesong; Gao, Zhiqiang; Ma, Youjie; Qin, Zhenwei
Graphical abstract: Highlights: A novel GMPPT strategy based optimal current control for PV system is proposed. The indirect relationship between solar irradiance ( Si ), cell's temperature ( Ti ) and operating current at GMPP ( Ipmax ) has been found out. The characteristics of Pmax (output power at MPP)- S - T and Ipmax - S - T are thoroughly analyzed. The proposed method has adequate under partial shading conditions. Abstract: From the engineering cybernetics perspective, determining the output current of a solar cell corresponding to the global maximum power point (GMPP) under uniform variable environmental and partial shading (PS) conditions is essential for tracking the maximum power point. However, conventional methods could not effectively achieve this goal, and approaches for utilizing this information do not exist, including the output voltage or current and duty cycle at GMPP, in the control process. This paper describes a novel algorithm for global maximum power point tracking (GMPPT) control in parameter optimization corresponding to variable environmental and PS conditions. In the proposed method, a definable nonlinear relation has been found between variable environmental parameters and the output current of solar arrays at every maximum power point. Additionally, this research gives the mathematical expression for it. Then, GMPPT control rules are created based on the findings from the nonlinear relation that can respond at high speeds to variations in irradiation and temperature of each solar cell and even at partial shading conditions. Therefore, MATLAB®/Simulink® numerical simulations are presented to illustrate that this control algorithm can implement the GMPPT of a PV generation system efficiently even in the variable environmental with partial shading conditions